Effect of two dehydration processes on extracts from Opuntia atropes and characterization of polyphenolic compounds by ultra high-resolution liquid chromatograph coupled with mass spectrometry - Eunice Tranquilino-Rodríguez (Taylor & Francis Group, 2021)
The objective of this research was to evaluate the polyphenolic compounds, the antioxidant activity, and the individual identification of the different types of phenolic compounds in dried extracts of Opuntia atropes. O. atropes extract was dehydrated in a drying oven at 50°C/24 h and by nano-spray drying at 105°C. Drying by nano-spray did not affect the content of phenolic compounds or the antioxidant activity of the O. atropes extract, presenting values of 11.80 ± 0.61 mg of gallic acid equivalent/g of phenolic acids, 22.26 ± 1.02 mg quercetin equivalent/g of flavonoids and inhibition percentage of the radical DPPH• (2,2-. diphenil-1-picrilhidrazil) and ABTS•+ (2,2ʹAzinobis(3-ethylbenzothiazoline-6 sulfonic acid)) of 17.92 ± 0.31 and 54.08 ± 0.48, respectively. In the powdered extracts of O. atropes, glycosides of kaempferol and isorhamnetin were mainly identified by ultra high-performance liquid chromatography coupled to mass spectrometry. Mediorresinol lignan was identified for the first time in this Opuntia species.